Evaluating the efficacy of digital design platform in improving public speaking proficiencies / Nurfazlina Haris ... [et al.] - Haris, Nurfazlina; Nik Fauzi, Sheela Faizura; Jalil, Susana William; Yusuf, Muhammad Jastu; Mahdi, Asmahani (UiTM Press, 2025)
In the wake of COVID-19, educational institutions worldwide rapidly shifted from traditional in-person instruction to fully virtual or hybrid classrooms. This study investigates the role of multimedia design guided by the Cognitive Theory of Multimedia Learning (CTML) in enhancing student engagement within an online Public Speaking course at UiTM Sarawak, Malaysia. Specifically, three CTML components are examined: video animation, video organization, and working memory overload. A purposive sampling approach yielded 103 student participants, representing an 80.62% response rate. Data was collected via a structured questionnaire comprising 22 items adapted from established CTML and engagement scales. Descriptive and inferential statistics, including Pearson’s correlation and multiple regression, were employed to analyse the relationships between the CTML factors and student cognitive engagement.